Comparative Analysis Of Asset Turnover And Capital Structure on Company Performance (Empirical Study Of Retail Companies in Indonesia and Thailand) - Brahmantyo Aryo Putra Salam; Loggar Bhilawa (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research aims to compares the effects of capital structure, as determinded by det to equity ratio (DER), and asset turnover (ATO), on business performance, as determined by return on asset (ROA), in retail prises in Indonesia and Thailand for the year 2024. This study also aims to ascertain whether the two countries average ATO, DER, and ROA are different. This study’s quantitative methodology makes use of secondary data from retail enterprises financial statements that are listed in the OSIRIS database. Purposive sampling was used to pick the 65 companies that made up the research sample. Among the analyticas techniques used are descriptive statistics, multiple linear regression analysis, classical assumption tests, hypothesis testing, and independent T-Test samples. The findings demonstrated that ATO had no appreciable benefical impact on ROA in either Thailand or Indonesia. Additionally, DER did not significatly have a negative impact on ROA in Indonesia nevertheless, in Thailand DER had a significant impact, but the regression coefficient’s direction was potivie, defying the premise. The average ATO and DER did not change significantly between the two nations, according to independent testing of the T-Test. However, the average ROA did differ significantly with Thailand retail profitability outperforming indonesia.